Promoting mental health and wellbeing in schools: the impact of yoga on young people's relaxation and stress levels - Hagen, Ingunn; Skjelstad, Solbjørg; Nayar, Usha Sidana (Frontiers in Psychology, 2023)
This study aimed to examine students' experiences with yoga interventions in school. The findings revealed that practicing yoga made young people more aware of their need to relax and positively impacted their mental health and wellbeing. We explored the emphasis on relaxation among our study participants and how relaxation is related to other aspects, such as their experience of stress and sleep habits. This article is based on qualitative data gathered from teenagers in Norway who participated in the Norwegian part of the European research project “Hippocampus: Promoting Mental Health and Wellbeing among Young People through Yoga.” The project introduced yoga to young people in schools with an emphasis on those who were disadvantaged, including those with mental health issues and other challenges related to their background. Data were collected from nine individual, semi-structured interviews and 133 logs collected in the spring of 2019.1 The major themes identified through the interviews and log material included becoming more relaxed and aware of the need to unwind. Thus, the focus on relaxation is based on the importance of the participants assigned to this theme. The study results suggest that yoga enhanced the students' awareness and skills and empowered them to make healthier lifestyle choices.2 We viewed the importance of relaxation from a salutogenic perspective, focusing on the factors that contribute to good health in contrast to a pathogenic perspective, where curing diseases is the goal.